The Binary Code: Notes on the Celebrating of Homosexuality: Бинарниот код: Белешки за славењето на хомосексуалноста - Panayotov, Stanimir; Hadjidochev, Petar; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Stanimir Panayotov | Станимир Панајотов Title (English): The Binary Code: Notes on the Celebrating of Homosexuality Title (Macedonian): Бинарниот код: Белешки за славењето на хомосексуалноста Translated by (Bulgarian to English): Petar Hadjidochev | Петар Хаџидочев Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 165-178 Page Count: 13 Citation (English): Stanimir Panayotov, “The Binary Code: Notes on the Celebrating of Homosexuality,” translated from the Bulgarian by Petar Hadjidochev, Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 165-178. Citation (Macedonian): Станимир Панајотов, „Бинарниот код: Белешки за славењето на хомосексуалноста“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 165-178.